Pemikiran Politik Islam: Suatu Pengantar Awal - Agus Nugraha (Refleksi: Jurnal Kajian Agama dan Filsafat, 2002)
History has recorded that during the medieval period, for approximately seven centuries, Islam flourished as a dominant global civilization, excelling in various fields of knowledge. Prominent Muslim scholars contributed significantly to diverse disciplines, such as Ibn Sina in medicine, al-Khwarizmi in mathematics, Ibn Khaldun in sociology, and Jabir ibn Hayyan in chemistry. Likewise, in the field of political thought, figures such as al-Farabi, al-Mawardi, al-Ghazali, and Ibn Taymiyyah made substantial contributions. During the reign of Caliph Harun al-Rashid (786–809 CE), Baghdad became the center of scientific study and the intellectual hub of the world. However, following the decline of the Islamic Caliphate and the rise of Western dominance, the influence of Muslim thinkers in global intellectual discourse significantly diminished, with Western thought becoming the primary reference in various fields. Given this historical shift, revisiting Islamic political thought is crucial for rediscovering the intellectual legacy established by early Muslim scholars. This paper does not aim to provide an in-depth analysis of Islamic political thought but rather to offer an introductory overview of its rich intellectual tradition.